Penerapan Edukasi Terstruktur Untuk Meningkatkan Kepatuhan Minum Obat Pada Pasien Hipertensi Di Wilayah Kerja Puskesmas Payung Sekaki Pekanbaru (JONAH : Journal of Nursing and Homecare, 2022)
Hypertension or high blood pressure is a disorder that occurs in the circulatory system, where a person is said to have hypertension if he has a systolic blood pressure exceeding 140 mmHg and a diastolic pressure more than 90 mmHg which can be measured using a sphygmomanometer. Patients with hypertension must adhere to taking medication so that blood pressure is stable and can avoid complications of the disease. Education is an independent nursing action that can improve medication adherence in hypertensive patients if it is carried out in a structured manner. The purpose of this case study is to describe the application of structured education to improve medication adherence in hypertension patients in the Payung Sekaki Public Health Center Pekanbaru. This research method is descriptive using a case study approach. The subjects of this study were two people with hypertension with the criteria of being 18 years old, having blood pressure ≥140/90 mmHg, having received hypertension drug therapy at Payung Sekaki Health Center and having a compliance level of ≤7. Analysis of medication adherence was carried out descriptively using the MMAS - 8 questionnaire. The results of the study showed that there was an increase in medication adherence in hypertensive patients after 2 weeks of structured education. subjects who had low adherence increased to high compliance. Recomendations for further research are to have good knowledge and skills in order to be able to educate the public, especially to patients with hypertension